Variations in phenolic acid metabolites among Forsythia suspensa populations in response to environmental heterogeneity - Zhou, Shanshan; Li, Zhengsen; Wang, Qingyu; Cao, Tianyu; Li, Danyang; Li, Kailu; Ji, Jinlan (Frontiers in Plant Science, 2025)
IntroductionForsythia suspensa (Thunb.) Vahl,a pharmacopoeial medicinal plant,is valued for its therapeutic efficacy in clearing heat and detoxifying, dispelling wind-heat, and promoting blood circulation to resolve stasis. Phenolic acids, ubiquitous secondary metabolites in F. suspensa, are critically linked to pharmacological activities and exhibit diverse biological functions.It is therefore of significant interest to investigate whether environmental changes also alter the content distribution of phenolic acids in F. suspensa.MethodsTo elucidate the chemical diversity and ecological drivers of its bioactive compounds, we conducted phenolic acids metabolomic profiling across 10 wild populations F. suspensa using UPLC-MS/MS.ResultsResults showedsignificant inter-population variation in all thirty phenolic acids analyzed. Specifically, Verbascoside was significantly enriched in the AZ population, showing a positive correlation with Mean Monthly Temperature Range, Temperature Seasonality, and Temperature Annual Range, but a negative correlation with Annual Precipitation, Precipitation of Driest Quarter, Precipitation of Coldest Quarter and Min Temperature of Coldest Month. 4-Coumaroylshikimate, accumulated in WML and PS, was positively correlated with Precipitation of Wettest Month, Precipitation of Wettest Quarter, and Precipitation of Warmest Quarter, while negatively correlated with Min Temperature of Coldest Month. Gallotannin, enriched in LT, was negatively correlated with Mean Monthly Temperature Range, Temperature Seasonality, Temperature Annual Range, and Precipitation Seasonality, but positively correlated with Annual Precipitation. Isosalicin, accumulated in HX, showed a positive correlation with Max Temperature of Warmest Month and negative correlation with Annual Precipitation and Elevation. DiscussionThese findings demonstrated that phenolic acids accumulation in F. suspensa was primarilydriven by temperature heterogeneity, with precipitation as a secondary factor, whereas adaptation to elevation plays a minimal role. This study systematically investigated the divergence and environmental drivers of phenolic acids in F. suspensa populations, clarifying the molecular ecological mechanisms behind its adaptation toenvironmental heterogeneity and thereby offering important insights into how ecological factors shape the medicinal potential of F. suspensa, ultimately informing targeted breeding and optimized field management.